Faktor Risiko Kepatuhan Kemoterapi pada Pasien Kanker Payudara - Halimatussakdiah, Halimatussakdiah; Junardi, Junardi (Jurnal Kesehatan, 2017)
The prevalence of cancer in Indonesia is significantly high. Based on data (Rikesdas) in 2013, it showed that the prevalence of cancer is 1,4 per 1000 people or approximately 330.000 people. The most popular cases faced by women is chest and cervix cancer. Data has shown that 75% of breast cancer had chemotherapy. The result of studies shows that more than 60% of chemotherapy patient caused hair fall, darken-nail, queasy, and loss appetite. The aim of this study was to find out factors related to the obedience to chemotherapy on breast cancer patients in wardThursina II BLUD Zainal Abidin Hospital Banda Aceh in 2017. This research was conducted from 1 April to 30 May 2017. This type of research was the correlation with crossectional study design approach. The population of the study included all of the breast cancer patients who were having chemotherapy. The technique of sampling used was accidental sampling that involved 65 participants. Data were analyzed using Chi-Square Test. The result of the study showed that there was a relationship self-concept and chemotherapy obedience (p-value=0,013); expense and chemotherapy obedience (p-value=0,036); family support and chemotherapy obedience (p-value=0,002); side-effects and chemotherapy obedient (p-value=0,007). It is hoped that all the employee in BLUD dr.Zainal Abidin Hospital Banda Aceh can improve nursing management and enhance operational standard procedure on chemotherapy for patients, especially for breast cancer patients.